THE IMPACT OF APPLYING ENTERPRISE RESOURCE PLANNING (ERP) SYSTEMS IN THE GOVERNMENT ACCOUNTING SYSTEM ON OPERATIONAL EFFICIENCY: AN ANALYTICAL STUDY IN A SAMPLE OF IRAQI UNIVERSITIES - Hamzah N. Al-Jumaili (Scholar Express Journals, 2025)
The purpose of this research is to investigate the effect of ERP systems in government accounting on Iraqi university operational efficiency and testing the role of the mediating effectiveness of accounting information system in that effect. The research took place in the environment of Iraqi universities; Anbar and Al-Sarraj Universities, to be exact. There were 99 data used in both universities, and their views on the items of the questionnaire prepared by the researchers as a tool for conducting it to reach its objectives and test hypotheses. The utilized methodology was a quantitative analysis with path coefficients through structural equation modeling. The study concluded that ERP systems have a strong significant impact on the effectiveness of accounting information system and operational efficiency, as well as accounting information quality will add value to organizational performance. In the questionnaire, system integration, accuracy of information, speed of accounting process and efficiency in reporting were named as variables most affecting implementation (now on three different aspects), compared to training, technical support and user adoption which had been regarded having the least impact meaning that there is a need for improving not only human resources but also infrastructure. The research concludes that implementation of Enterprise Resource Planning (ERP) is contributing to positive financial and administrative performance. To maximize the gains there is need to improve accounting information systems, a conducive technological change environment and increasing training and development, integration of interdepartmental operations and e-government to enhance transparency and sustainability. Moreover, future studies suggest investigating the long-term effect of such systems on organizational performance and considering other mediating and controlling variables such as digital transformation, managerial innovation and the quality of strategic decisions.
Keywords: Enterprise Resource Plannin; systems; accounting system